LU-HF SYSTEMATICS OF THE ULTRA-HIGH TEMPERATURE NAPIER METAMORPHIC COMPLEX IN ANTARCTICA: EVIDENCE FOR THE EARLY ARCHEAN DIFFERENTIATION OF EARTH'S MANTLE - Choi S.H.; Mukasa S.B.; Andronikov A.V.; Osanai Y.; Harley S.L.; Kelly N.M. (My University, 2006)
The Napier Complex of the East Antarctic Craton comprises some of the oldest rocks on Earth (~ 3.8 billion years old), overprinted by an ultra-high temperature (UHT) metamorphic event near the Archean-Proterozoic boundary. Garnet, orthopyroxene, sapphirine, osumilite, rutile and a whole rock representing a fully equilibrated assemblage from this UHT granulite belt have yielded a Lu-Hf isochron age of 2403 ± 43 Ma, the first ever determined on a UHT mineral assemblage. Preservation of the UHT mineral assemblage in the rock analyzed, without any significant retrogression, suggests rapid cooling with closure likely to have occurred for the Lu-Hf system at post-peak UHT conditions near a temperature of ~ 800 °C. This mineral-whole rock isochron yields an initial 176Hf/177Hf ratio corresponding to an εHf value of - 14 ± 1, acquired during UHT metamorphism. Such a low value demonstrates that overall UHT granulites evolved in a low Lu/Hf environment, probably formed when the rocks were first extracted from a highly depleted mantle. Zircon εHf values we have measured "see through" the UHT metamorphism and show that the source materials for the magmas that formed the Napier Complex were extremely depleted (> + 5.6 εHf at 3.85 Ga) relative to the chondritic uniform reservoir (CHUR). These results also suggest significant depletion of the early Archean mantle, in agreement with the early differentiation of the Earth that the latest core formation models require. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANTARCTICA; ARCHEAN; LU-HF ISOTOPE; NAPIER COMPLEX; UHT GRANULITE; ZIRCON; Докембрий::Архей; Precambrian::Archean